Earth Science - Marshak, Stephen; Rauber, Robert (New york : W W Norton & Company, 2020)
Whether hiking along a mountain trail, driving down a highway, or making a decision about their energy usage, instructors want their students to see and assess the physical world they live in with more informed eyes. Through the most contemporary and applied text; the most vibrant visuals; and the most hands-on learning resources, Earth Science, Second Edition gets students leaving the class with a richer understanding of the science behind the physical world around them, and why it matters in their everyday lives.
Includes index and glossary.
Keywords: Astronomy; 9; Climate change; Earth sciences